Correlations between intake and ingestive behavior of supplemented pasture-finished steers - Angélica Francelina Sampaio; Fabrício Bacelar Lima Mendes; Robério Rodrigues Silva; Túlio Otávio Lins; Hermógenes Almeida de Santana Júnior (Acta Scientiarum. Animal Sciences, 2025)
The objective was to evaluate the correlations between intake and ingestive behavior of steers receiving supplementation and finished on pasture. The field phase was conducted at the Princesa do Mateiro Farm, municipality of Ribeirão do Largo, state of Bahia. For this experiment, 32 crossbred steers (Holstein X Zebu) in the finishing phase, with an average initial weight of 420 ± 7.54 kg, were distributed in a completely randomized design, with four treatments (0.2, 0.4, 0.6, and 0.8%) and eight repetitions. Grazing time (GT) did not correlate (p > 0.05) with total dry matter intake (TDMI). GT showed a moderate positive correlation (p < 0.05) with crude protein intake (CPI) and neutral detergent fiber intake corrected for ash and protein (NDFIap). Rumination time (RUM) showed a weak negative correlation (p < 0.05) with NFCI. Trough feeding time (TFT) showed moderate negative correlations with NDFIap and moderate positive correlations with NFCI (p < 0.05). The number of bites per day (NBD) showed a weak negative correlation with TDMI and a moderate negative correlation with CPI, NDFIap (p < 0.05). The correlations found demonstrate that supplementation of steers finished on pasture interferes with their ingestive behavior.